EXAMINING SOME INSTITUTIONAL FRAMEWORK ON ENVIRONMENTAL POLLUTION IN NIGERIA - Zekeri Glory Ojomachewu; ThankGod Okeokwo (PT ANTIS International Publisher, 2024)
Institutions are established to uphold certain programmes of government which are helpful for development of the human society. The control of pollution activities of individuals and corporate organizations are some of the concerns of modern day world. Diligence and compliance with rules will assist institutions perform optimally. However, innovation and technology can aid in carrying out functions and achieving set goals efficiently. This paper focuses on institutional framework on environmental pollution in Nigeria. To prevent destruction of environmental resources through pollution, institutions like the NESREA and National Council for Climate Change are established. Statute like National Environmental Standards and Regulations Enforcement Agency Act 2007 as amended and Climate Change Act 2021 created institutions to promote anti-pollution campaign. It was found that environmental pollution can be curtailed and climate change curbed if the institutions perform their duties with patriotism. It was recommended that Agencies like NESREA and National Council for Climate Change should synergise in areas of technical assistance and pollution remediation equipment acquisition and utilisation.